Functional assessment of strains around a full-thickness and critical sized articular cartilage defect under compressive loading using MRI. Issue 12 (December 2018) - Zevenbergen, L.; Gsell, W.; Chan, D.D.; Vander Sloten, J.; Himmelreich, U.; Neu, C.P.; Jonkers, I.
Summary: Objective: The objective of this study was to evaluate the effect of full-thickness chondral defects on intratissue deformation patterns and matrix constituents in an experimental model mimicking in vivo cartilage-on-cartilage contact conditions. Design: Pairs of bovine osteochondral explants, in a unique cartilage-on-cartilage model system, were compressed uniaxially by 350 N during 2 s loading and 1.4 s unloading cycles (≈1700 repetitions). Tissue deformations under quasi-steady state load deformation response were measured with displacement encoded imaging with stimulated echoes (DENSE) in a 9.4 T magnetic resonance imaging (MRI) scanner. Pre- and post-loading, T 1, T 2 and T 1 ρ relaxation time maps were measured. We analyzed differences in strain patterns and relaxation times between intact cartilage ( n = 8) and cartilage in which a full-thickness and critical sized defect was created ( n = 8). Results: Under compressive loading, strain magnitudes were elevated at the defect rim, with elevated tensile and compressive principal strains ( Δ ϵ max = 4.2%, P = 0.02; Δ ϵ min = −4.3%, P = 0.02) and maximum shear strain at the defect rim ( Δ γ max = 4.4%, P = 0.007). The opposing cartilage showed minimal increase in strain patterns at contact with the defect rim but decreased strains opposing the defect. After defect creation, T 1, T 2 and T 1 ρ relaxation times were elevated at the defect rim only. Following loading, the overall relaxations times of the defect tissue and especially at the rim, increased compared to intact cartilage. Conclusions: This study demonstrates that the local biomechanical changes occurring after defect creation may induce tissue damage by increasing shear strains and depletion of cartilage constituents at the defect rim under compressive loading.